2007
DOI: 10.2337/db06-0440
|View full text |Cite
|
Sign up to set email alerts
|

Role for Mitochondrial Reactive Oxygen Species in Brain Lipid Sensing

Abstract: The ability for the brain to sense peripheral fuel availability is mainly accomplished within the hypothalamus, which detects ongoing systemic nutrients and adjusts food intake and peripheral metabolism as needed. Here, we hypothesized that mitochondrial reactive oxygen species (ROS) could trigger sensing of nutrients within the hypothalamus. For this purpose, we induced acute hypertriglyceridemia in rats and examined the function of mitochondria in the hypothalamus. Hypertriglyceridemia led to a rapid increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 65 publications
8
88
0
1
Order By: Relevance
“…In recent years, abundant research demonstrates that elevated ROS production causes cellular dysfunction and death, whereas normal ROS levels produced in mitochondria are required as a vital physiological sensor for hypothalamic glucose and fatty acid sensing [31, 32]. The ability of hypothalamic neurons to sense glucose is crucial to maintain body weight and control obesity [33].…”
Section: Hypothalamic Ros Regulates Glucose and Fatty Acid Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, abundant research demonstrates that elevated ROS production causes cellular dysfunction and death, whereas normal ROS levels produced in mitochondria are required as a vital physiological sensor for hypothalamic glucose and fatty acid sensing [31, 32]. The ability of hypothalamic neurons to sense glucose is crucial to maintain body weight and control obesity [33].…”
Section: Hypothalamic Ros Regulates Glucose and Fatty Acid Sensingmentioning
confidence: 99%
“…The authors found that the elevated hypothalamic ROS modified the redox state of oxidized and reduced glutathione but failed to cause oxidative stress measured by dichlorofluorescein fluorescence ex vivo . These authors concluded that acute hypertriglyceridemia triggered hypothalamic ROS production due to the increased mitochondrial activity [32]. …”
Section: Hypothalamic Ros Regulates Glucose and Fatty Acid Sensingmentioning
confidence: 99%
“…Oxidative stress has been reported to precede the appearance of insulin insensitivity in high-fat diet-induced obesity (140) . The induction of hypertryglyceridaemia in rats has been shown to increase mitochondrial respiration in the hypothalamus together with an increase in ROS production (141) . ROS have been shown to be important in both glucose and lipid sensing by the hypothalamus (141,142) and increased ROS in the hypothalamus of the Zucker fatty rat has been linked to abnormal glucose sensing (143) .…”
Section: Hypothalamic Oxidative Stressmentioning
confidence: 99%
“…The induction of hypertryglyceridaemia in rats has been shown to increase mitochondrial respiration in the hypothalamus together with an increase in ROS production (141) . ROS have been shown to be important in both glucose and lipid sensing by the hypothalamus (141,142) and increased ROS in the hypothalamus of the Zucker fatty rat has been linked to abnormal glucose sensing (143) . Indeed in the hypothalamus, the regulation of the melanocortin system requires the presence ROS as an acute activator of firing by POMC neurons resulting in decreased food intake, and suppression of ROS leads to activation of the AgRP/NPY neurons and increased feeding.…”
Section: Hypothalamic Oxidative Stressmentioning
confidence: 99%
“…Ainsi, même si le métabolisme des acides gras peut être nécessaire pour relayer leur effet, on peut aussi envisager des mécanismes d'action indépendants. On peut également signaler l'importance que pourrait jouer les espèces actives de l'oxygène dans la sensibilité centrale aux lipides, comme l'ont montré Benani et al [33]. Il serait également intéressant de parler de ces espèces actives de l'oxygène dans les effets délétères d'un apport excessif de lipides.…”
Section: Mécanismes Moléculaires Relayant L'effet Des Acides Grasunclassified